Statistical sunspots - William A. Branch; Bruce McGough; Mei Zhu (Theoretical Economics, 2022)
This paper shows that belief-driven economic fluctuations are a general feature of many determinate macroeconomic models. In environments with hidden state variables, forecast-model misspecification can break the link between indeterminacy and sunspots by establishing the existence of "statistical sunspots" in models that have a unique rational expectations equilibrium. To form expectations, agents regress on a set of observables that can include serially correlated nonfundamental factors (e.g., sunspots, judgment, expectations shocks, etc.). In equilibrium, agents attribute, in a self-fulfilling way, some of the serial correlation observed in data to extrinsic noise, i.e., statistical sunspots. This leads to sunspot equilibria in models with a unique rational expectations equilibrium. Unlike many rational sunspots, these equilibria are found to be generically stable under learning. Applications are developed in the context of a New Keynesian and an asset-pricing model.
Keywords: D82; D83; E40; E50; 330; Adaptive learning; animal spirits; business cycles; optimal monetary policy